Nudges in Latin America? Affect Individual Behavior to Get Collective Results - Güemes, Cecilia (Revista del CLAD Reforma y Democracia, 2017)
This article describes a technology that seeks to improve the effectiveness of public policies in order to achieve their goals. Improve the efficiency of governance, increase social trust and the latter enhance cooperation and collective action that governance demands. Nudge acts by reconfiguring the decision architecture; this tool calls into question the model of rational agent, revaluing the automatic system of action, emotions and shared mental schemas. The proposed outline is as follows: first, it describes the innovative environment and the human behavior model on which the nudges develop. Second, the tool is develops and political efforts in Anglo-Saxon countries to institutionalize their design are presented. Third, the paper contrasts the enthusiasm for this technology with its limits and systematizes its criticisms. Finally, the opportunity of this proposal is analyzed in the framework of the complexities that face Latin America.
Keywords: Public Policy; Efficiency; Latin America